Comparison of Effectiveness of Strontium Ranelate and Alendronate Sodium in Postmenopausal Osteoporosis - Original Investigation - Kurtuluş Kaya; Sibel Ünsal Delialioğlu; Sumru Özel; Canan Çulha; Eda Kurt; Sezen Özgönül (Galenos Yayinevi, 2009)
Aim: Comparison of the effectiveness of strontium ranelate (SR) and alendronate sodium (AS) on bone mineral density (BMD) in postmenopausal osteoporosis. Material and Methods: A total of 41 patients were included in the study. 2 gr/day SR was applied a group (SR, n=21), while the other group received 70 mg/week AS randomly (AS, n=20). Both groups received daily doses of 1200 mg calcium+800 IU vitamin D3. BMD was measured before treatment (BT) and at the 6th and 12th months after treatment (AT) using dual energy x-ray absorptiometry. Lumbar spine (L2-L4), femoral neck and femoral total BMD values were recorded. 15 of the patients who received SR treatment (n=21) came for AT 6th month, and 17 of them came for AT 12th month follow-up, while 10 of patients receiving AS treatment (n=20) came for AT 6th month, and 7 came for AT 12th month follow-up. On the other hand, twenty patients (SR n=13, AS n=7) came for both 6th and 12th month follow-up. Results: Age, body mass index, and BT BMD values in all regions were similar (p>0.05). When BMD values at AT6th and AT12th months were compared with BT values, it was found that SR produced significant increases in BMD values of all regions examined (p<0.05); and that AS produced significant increase at femoral neck and lumbar spine BMD values (p<0.05) while it did not produced significant increase in femoral total BMD values. No significant difference was found between two groups with respect to BMD values between AT6th and AT12th months (p>0.05). Conclusion: It has been found that both SR and AS produced significant increases in femoral neck and lumbar spine BMD values at AT12th months, while SR is found to be more effective than AS on femoral total BMD values. (From the World of Osteoporosis 2009;15:70-4)